Peran Guru dalam Membentuk Jiwa Kewirausahaan Siswa melalui Program Business Day di SDI Baiturrahman Bagor - Siti Ismi Wulandari; Arif Mansyuri; Nur Kholis (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The Indonesian economy is facing serious challenges such as financial instability, high unemployment and the threat of a middle income trap. To overcome this, it is necessary to develop human resources that are oriented towards entrepreneurship. Education is the key in creating creative, innovative and tough individuals. This research aims to examine the role of teachers in forming students' entrepreneurial spirit through the